Rate of atypical nodal metastases in surgically treated HPV‐associated oropharyngeal squamous cell carcinoma. Issue 2 (23rd November 2022) - Miller, Lauren E.; Au, Vivienne H.; Sivarajah, Shanmugappiriya; Lin, Derrick T.; Deschler, Daniel G.; Varvares, Mark A.; Faden, Daniel L.; Feng, Allen L.; Sadow, Peter M.; Richmon, Jeremy D.
Abstract: Background: Understanding of nodal metastasis in patients with HPV+ oropharyngeal squamous cell carcinoma (OPSCC) is warranted. Methods: Patients with HPV+ OPSCC who underwent neck dissection (ND) between 2016 and 2021 were reviewed. Pathology reports were reviewed for lymph node (LN) metastases. Noncontiguous metastases were defined as pathologic evidence of level II disease with another involved LN in a noncontiguous neck level. Skip metastases were defined as pathologic lymph node(s) in the neck without disease in level II. Results: One hundred and thirty‐one patients underwent levels II–IV ND with a mean (SD) LN yield of 33.3 (±13.5). The rate of atypical metastases in both the therapeutic and elective ND cohort was 5%. The noncontiguous and skip metastases were in level IV ( n  = 2) and level III ( n  = 4), respectively. Conclusions: Skip and noncontiguous metastases were rare in patients with HPV+ OPSCC undergoing surgical treatment. Surgeons may consider a selective ND omitting Level IV in select patients with HPV+ OPSCC undergoing surgery.